Pentingnya Karakteristik Murid Kristus bagi Jemaat menurut Kisah Para Rasul 2:41-47 - Nelly Nelly; Murni Yanti (Sekolah Tinggi Alkitab Jember, 2021)
The success of God's work and ministry carried out by the early church centered on the characteristics of the early church who were disciples of Christ. The church today needs to pay attention to the principle developed by the early church, namely, the characteristics of the disciples of Christ. This article aims to show the important characteristics of Christ's disciples through reading Acts 2: 41-47. By using the descriptive analysis method, several characteristics mentioned in the text are obtained, namely: perseverance, prayer, and unity. In conclusion, believers, congregations, or those who call themselves disciples of Christ, must have characteristics that make them different from people who only follow God as a mere religious obligation.AbstrakKeberhasilan pekerjaan Tuhan dan pelayanan yang dilakukan oleh gereja mula-mula berpusat pada karakteristik jemaat mula-mula yang adalah murid Kristus. Gereja masa kini perlu memerhatikan prinsip yang dikembangkan oleh gereja mula-mula, yakni karakteristik murid Kristus. Artikel ini bertujuan untuk menunjukkan pentingnya karakteristik murid Kristus melalui pembacaan Kisah Para Rasul 2:41-47. Dengan menggunakan metode analsis deskriptif diperoleh beberapa karakteristik yang disebut pada teks tersebut, yakni: bertekun, berdoa, dan bersatu. Kesimpulannya, orang percaya, jemaat, atau yang menyebut dirinya sebagai murid Kristus, harus memiliki karakteristik yang menjadikannya berbeda dengan orang yang hanya mengikut Tuhan sebagai kewajiban agamawi belaka.